2015
DOI: 10.1530/erc-14-0516
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinases and the new therapeutic opportunities offered to cancer

Abstract: Deubiquitinases (DUBs) play important roles and therefore are potential drug targets in various diseases including cancer and neurodegeneration. In this review, we recapitulate structure-function studies of the most studied DUBs including USP7, USP22, CYLD, UCHL1, BAP1, A20, as well as ataxin 3 and connect them to regulatory mechanisms and their growing protein interaction networks. We then describe DUBs that have been associated with endocrine carcinogenesis with a focus on prostate, ovarian, and thyroid canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
126
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 213 publications
(232 reference statements)
0
126
0
1
Order By: Relevance
“…Furthermore, increased A20 expression or activity has also been associated with dampening numerous disease outcomes (29,30). Thus, there is great interest in manipulating A20 for therapeutic benefit (31). In regard to the TLR pathways, prior studies have identified cross talk between TLR9, TLR2, and TLR4 in both periodontitis and other disease models (18,32).…”
Section: Tlr9 and A20 In Periodontal Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, increased A20 expression or activity has also been associated with dampening numerous disease outcomes (29,30). Thus, there is great interest in manipulating A20 for therapeutic benefit (31). In regard to the TLR pathways, prior studies have identified cross talk between TLR9, TLR2, and TLR4 in both periodontitis and other disease models (18,32).…”
Section: Tlr9 and A20 In Periodontal Inflammationmentioning
confidence: 99%
“…It is possible that, although it is still a functional protein in the course of periodontitis, A20 expression does not reach sufficient levels to facilitate the resolution of inflammation. Thus, the questions that remain to be answered are how A20 levels and activity are regulated and whether the manipulation of A20 can prevent further periodontal tissue destruction, similar to its effects in other inflammatory diseases (29)(30)(31).…”
Section: Tlr9 and A20 In Periodontal Inflammationmentioning
confidence: 99%
“…The pharmacological inhibition of ubiquitin-proteasome molecular targets, to modulate the stability of tumor suppressor proteins, has received increased interests [20]. Early studies on USP7 inhibition have shown antitumor properties in multiple myeloma [21], in neuroblastoma [22] and in p53 wild-type and null isogenic cancer cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…(D'Arcy et al, 2015; Pfoh et al, 2015). UPS consists of a tagging molecule–ubiquitin and a multi-subunit proteolytic complex–the 26S proteasome.…”
Section: Introductionmentioning
confidence: 99%